2018
DOI: 10.1101/471045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PTPN14 Degradation by High-Risk Human Papillomavirus E7 Limits Keratinocyte Differentiation and Contributes to HPV-Mediated Oncogenesis

Abstract: 2 6 2 7 Classification: Biological Sciences / Microbiology 2 8 Abstract 3 0High-risk human papillomavirus (HPV) E7 proteins enable oncogenic transformation of HPV-3 1 infected cells by inactivating host cellular proteins. High-risk but not low-risk HPV E7 target 3 2 PTPN14 for proteolytic degradation, suggesting that PTPN14 degradation may be related to 3 3 their oncogenic activity. HPV infects human keratinocytes but the role of PTPN14 in 3 4 keratinocytes and the consequences of PTPN14 degradation are unknow… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 96 publications
5
15
0
Order By: Relevance
“…PTPN14 or PTPD2 is a cytosolic protein that contains an N-terminal four-point-one, ezrin-radixin-moesin (FERM) domain, central proline-rich motifs, and a C-terminal catalytic PTP domain. Given that PTPN14 is an important antitumor protein that cooperates with the p53 transcription factor and negatively regulates Hippo signaling-involved cell proliferation (Huang et al, 2013;Liu et al, 2013;Mello et al, 2017;Michaloglou et al, 2013;Wilson et al, 2014), it is not surprising that this protein is targeted by HPV E7 via direct binding, which leads to its proteasomal degradation (Hatterschide et al, 2019;Szalmas et al, 2017;White et al, 2016;Yun et al, 2019). Our previous study also revealed that PTPN21 or PTPD1 can directly interact with CR3 of HPV18 E7 (Yun et al, 2019), consistent with previous systematic proteomic analyses (Rozenblatt-Rosen et al, 2012;White et al, 2012).…”
Section: Introductionsupporting
confidence: 87%
“…PTPN14 or PTPD2 is a cytosolic protein that contains an N-terminal four-point-one, ezrin-radixin-moesin (FERM) domain, central proline-rich motifs, and a C-terminal catalytic PTP domain. Given that PTPN14 is an important antitumor protein that cooperates with the p53 transcription factor and negatively regulates Hippo signaling-involved cell proliferation (Huang et al, 2013;Liu et al, 2013;Mello et al, 2017;Michaloglou et al, 2013;Wilson et al, 2014), it is not surprising that this protein is targeted by HPV E7 via direct binding, which leads to its proteasomal degradation (Hatterschide et al, 2019;Szalmas et al, 2017;White et al, 2016;Yun et al, 2019). Our previous study also revealed that PTPN21 or PTPD1 can directly interact with CR3 of HPV18 E7 (Yun et al, 2019), consistent with previous systematic proteomic analyses (Rozenblatt-Rosen et al, 2012;White et al, 2012).…”
Section: Introductionsupporting
confidence: 87%
“…More recently, the interaction between E7 and UBR4 was found to be required for PTPN14 degradation and that this contributes towards delaying keratinocyte differentiation, as discussed previously in this section [212][213][214]. However, PTPN14 knockout also reduced detachmentinduced cell death, perhaps indicating that targeting of this pathway by HPV may concurrently impact upon differentiation and anoikis [214].…”
Section: Resistance To Anoikismentioning
confidence: 67%
“…A diverse range of E7 proteins possess the ability to bind the non-receptor protein tyrosine phosphatase PTPN14, with HR-HPV E7 proteins additionally able to target it for proteasomal degradation using the UBR4 ubiquitin ligase [212,213]. This loss of PTPN14 is critical in both delaying the epithelial differentiation programme and for cellular transformation, although evidence that this is achieved via modulation of Hippo pathway signalling remains controversial [214,215]. Interestingly, mutational analyses indicate that this constitutes one of the as yet poorly defined pRb-independent functions of E7: regions in both CR1 and the C-terminus are necessary for formation of the E7/PTPN14/UBR4 complex.…”
Section: Impairment Of Differentiationmentioning
confidence: 99%
“…The HPV E6 protein prevents the YAP1 protein from undergoing proteasome‐mediated degradation 41 . HPV E7 protein binds to and targets PTPN14 for proteasome‐mediated degradation, which likely relieves the cytoplasmic retention of YAP by PTPN14 43,44 . This combination of HPV E6/E7‐induced accumulation of YAP protein plus its release to the nucleus leads to vigorous YAP activation that may promote human cervical epithelial cell proliferation and eventually CIS onset 23,42 .…”
Section: Links Between Hippo‐yap Signaling and Scc Onsetmentioning
confidence: 99%